Associations of Genetic Polymorphisms and Neuroimmune Markers With Some Parameters of Frontal Lobe Dysfunction in Schizophrenia - Morozova, Anna; Zorkina, Yana; Pavlov, Konstantine; Pavlova, Olga; Abramova, Olga; Ushakova, Valeria; Mudrak, Alexander V.; Zozulya, Svetlana; Otman, Irina; Sarmanova, Zoya; Klyushnik, Tatiana; Reznik, Alexander; et al. (Frontiers in Psychiatry, 2021)
We investigated the associations of DRD3 rs6280, HTR1A rs6295, BDNF rs6265, SCL6A4 rs16965628 and 5HT2A rs7322347 with schizophrenia in a case–control study, and associations of these genetic variants with several clinical features. We also investigated markers of inflammatory response (C-reactive protein, IL-2, IL-6, IL-10), the activity of leukocytic elastase (LE) and α1-proteinase inhibitor (a1-PI), antibodies to S100B and myelin basic protein (MBP) in schizophrenia. Clinical symptoms were assessed on three scales: Positive and Negative Syndrome Scale, The Bush – Francis Catatonia Rating Scale and Frontal Assessment Battery. All SNPs were typed using predesigned TaqMan SNP genotyping assays. The biomarkers related to the immune system were routinely tested using ELISA kits. The association with schizophrenia was found for DRD3 rs6280 (р=0,05) and HTR2A rs7322347 (p=0,0013). We found differences between groups by parameters of LE and a1-PI and LE/a1-PI (р<0,001). And IL-6 was evaluated in the schizophrenia group (р<0,001). We showed that patients with the TT allele (BDNF rs6265) had more severe impairments in frontal lobe function. a1-PI can serve as a marker for assessing the severity of frontal lobe damage in patients with frontal dementia. We found some biological parameters reflecting the severity of frontal dysfunction in schizophrenia. Keywords: schizophrenia, PANSS, FAB, DRD3, BDNF, HTR2A, leukocyte elastase, α1-proteinase inhibitor